DIMENSI ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Badaruddin Badaruddin (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2022)
The purpose of this study was to determine the effect of the variables of leadership, job satisfaction and organizational commitment on organizational citizenship behavior at the Indonesian Nobel Institute of Technology and Business. This study uses quantitative methods, namely data collection techniques obtained from the results of questionnaires distributed. The population of this study were lecturers at the Nobel Indonesia Institute of Technology and Business as many as 50 people with a saturated sample technique so that the total sample was 50 people. The data collection technique in this research uses a questionnaire with a scale of measurement for the research instrument using a Likert scale. To examine the relationship between the independent variable and the dependent variable in this study, multiple linear analysis was carried out through the SPSS V. 26 program. The results of this study found that leadership, job satisfaction and organizational commitment both partially and simultaneously have a positive and significant effect on Organizational Citizenship Behavior (OCB) lecturer at the Nobel Indonesia Institute of Technology and Business